Trends in general and abdominal obesity in US adults: Evidence from the National Health and Nutrition Examination Survey (2001–2018) - Sun, Jin-Yu; Huang, Wen-Jun; Hua, Yang; Qu, Qiang; Cheng, Chen; Liu, Heng-Li; Kong, Xiang-Qing; Ma, Yong-Xiang; Sun, Wei (Frontiers in Public Health, 2022)
Aim This study investigates the trend in general obesity and abdominal obesity in US adults from 2001 to 2018. Methods We included 44184 adults from the nine cycles of the continuous NHANES (2001-2002, 2003-2004, 2005-2006, 2007-2008, 2009-2010, 2011-2012, 2013-2014, 2015-2016, 2017-2018). The age-adjusted mean body mass index and waist circumference were calculated, and the sex-specific annual change was estimated by the survey cycle. We used the weighted sex-specific logistic regression models to analyze the prevalence of general obesity and abdominal obesity from 2001 to 2018. The weighted adjusted odds ratio (OR) with a 95% confidence interval (CI) was calculated. Results Our study showed that general obesity and abdominal obesity account for about 35.48% and 53.13% of the US population. From 2001-2002 to 2017-2018, the age-adjusted prevalence of general obesity increased from 33.09% to 41.36% in females and from 26.88% to 42.43% in males. During 2001-2018, the age-adjusted prevalence of abdominal obesity increased from 57.58% to 67.33% in females and from 39.07% to 49.73% in males. A significant time-dependent increase was observed in the prevalence of general obesity (adjusted OR, 1.007; 95% CI 1.005-1.009, P < 0.001) and abdominal obesity (adjusted OR, 1.006; 95% CI, 1.004-1.008; P < 0.001). Conclusion General obesity and abdominal obesity are a heavy health burden among US adults, and the increasing trend remains in both males and females from 2001 to 2018.